2020
DOI: 10.1039/d0ra06890j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrochemical biosensing performance for Au nanoparticle–polyaniline–TiO2 heterojunction composites

Abstract: A novel photoelectrode for glucose PEC biosensing composed of TiONTAs, PANI, and AuNPs was successfully obtained. The GOx@Au–PANI–TiONTA electrode exhibited a wide response range (2–36 mM) with a low detection limit (0.02 mM) and good stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…For example, Ju and co-workers applied polyaniline (PANI)/titanium dioxide (TiO 2 ) nanotube composite to lactic acid photoelectric detection and obtained higher photocatalytic activity. Similarly, the previous research of our group has also shown that the addition of PANI effectively inhibits the recombination of photogenerated charges …”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, Ju and co-workers applied polyaniline (PANI)/titanium dioxide (TiO 2 ) nanotube composite to lactic acid photoelectric detection and obtained higher photocatalytic activity. Similarly, the previous research of our group has also shown that the addition of PANI effectively inhibits the recombination of photogenerated charges …”
Section: Introductionsupporting
confidence: 72%
“…Similarly, the previous research of our group has also shown that the addition of PANI effectively inhibits the recombination of photogenerated charges. 33 Herein, a photoelectrochemical platform was built based on polyaniline modified titanium dioxide facet heterojunction (FH-TiO 2 ) structures, and polyaniline was introduced into the FH structure as an electronic medium. Synthesis procedure and detection principle of the PANI@FH-TiO 2 electrode are presented in Scheme 1a.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode generated a photovoltage as photogenerated electron–hole pairs accumulated on the cathode and anode under illumination. 22 When the light was canceled, the photogenerated holes collected on the anode and the photogenerated electrons collected on the cathode quickly recombined, and then the open circuit potential was recorded. The lifetime of the photogenerated carriers could be calculated with formula (2) .…”
Section: Resultsmentioning
confidence: 99%
“…After loading the enzyme, the Au-PANI-TiONTA electrode showed a good response to glucose in the linear range of 2–36 mM, and the detection limit was 0.02 mM. 124…”
Section: Biosensing Applicationsmentioning
confidence: 95%
“…After loading the enzyme, the Au-PANI-TiONTA electrode showed a good response to glucose in the linear range of 2-36 mM, and the detection limit was 0.02 mM. 124 As mentioned above, AuNMs can be easily functionalized by various biomolecules and other organic chemicals, and this property is also studied by Li et al In their study, using DNA-functionalized AuNPs (DNA-AuNPs) to initiate the hybrid chain reaction (HCR), a novel label-free electrochemiluminescence (ECL) biosensor was established to detect thymine DNA glycosylase (TDG). Combined with the amplification function of DNA-AuNPs triggered HCR and the inherent high sensitivity of ECL technology, the detection limit for TGD was 1.1 × 10 −5 U μL −1 (0.0028 ng mL −1 ).…”
Section: Optical Biosensorsmentioning
confidence: 95%